A Multivariate Regression Model Between the October Rainfall Anomalies in Central America and the Tropical Pacific and Atlantic Ocean - Alfaro Martínez, Eric J. (1999)
Sugerencia para su referencia: Alfaro, E., 1999. “A Multivariate Regression Model Between the October Rainfall Anomalies in Central America and the Tropical Pacific and Atlantic Ocean”. Paper Presented in the First Workshop on Regional Climate Prediction and Applications-Tropical Atlantic Basin, staged by Cooperative Institute for Mesoscale Meteorological Studies, The University of Oklahoma, Norman, Ok, USA. October 11- November 12, 1999. College of Continuing Education, The University of Oklahoma, Norman, Ok, USA.